The handbook of risk (Wiley, 2003)
Before entering into any investment, the risk of that venture must be identified and quantified. The Handbook of Risk provides in-depth coverage of risk from every possible angle and illuminates the subject by covering the quantitative and and behavioral issues faced by investment professionals on a day-to-day basis. This valuable reference offers a prescriptive and descriptive treatment of risk management for those looking to control, contain, and minimize the risk of their investments.